Marketing Analytics Using Excel : A Beginner′s Guide - Kaurav, Rahul Pratap Singh (SAGE Publications, Ltd. (UK), 2025)
Marketing Analytics Using Excel is the essential introduction to data-driven marketing, which simplifies complex concepts and offers practical, real-world applications. This comprehensive yet accessible guide encourages an in-depth understanding of marketing analytics, from fundamental topics and basic Excel functions to more advanced topics such as AI and predictive analytics.  Packed with practical examples and easy-to-follow, fully worked problems which demonstrate how theoretical concepts are applied in real-world situations, this book also includes: Industry case studies from leading companies like Zappos, Amazon, Netflix, and Spotify, providing insights into how marketing analytics is applied in various industries. Exercises, activities and discussion questions to reinforce learning. A focus on open access tools and career prospects which encourages readers to develop further This no-nonsense guide minimises the intimidation factor of complex formulas and instead focuses on practical, real-world applications, making it essential reading for Marketing students and anyone looking to upskill. Dr Rahul Pratap Singh Kaurav is Associate Professor at FORE School of Management, New Delhi, India. Dr Asha Thomas is an Assistant Professor at Wroclaw University of Science and Technology (WUST), Poland.